FGFBP1 as a potential biomarker predicting bacillus Calmette–Guérin response in bladder cancer - Li, Fei; Zhang, Henghui; Wang, Yu; Yao, Zhihao; Xie, Kunfeng; Mo, Qixin; Fan, Qin; Hou, Lina; Deng, Fan; Tan, Wanlong (Frontiers in Immunology, 2022)
Accurate prediction of Bacillus Calmette-Guérin (BCG) response is essential to identify bladder cancer (BCa) patients most likely to respond sustainably, but no molecular marker predicting BCG response is available in clinical routine. Therefore, we firstly identified that Fibroblast growth factor binding protein 1 (FGFBP1) was up-regulated in failures to BCG therapy, and the increased FGFBP1 had a poor outcome for BCa patients in the E-MTAB-4321 and GSE19423 datasets. These different expression genes associated with FGFBP1 expression were mainly involved in neutrophil activation, neutrophil-mediated immunity and tumor necrosis factor-mediated signal pathways in biological processes. A significant positive correlation was observed between FGFBP1 expression and Tregs infiltration by Spearman correlation test in the BCG cohort (r=0.177) and the TCGA cohort (r=0.176), suggesting that FGFBP1 may influence the response of BCa patients to BCG immunotherapy through immune escape. Though FGFBP1 expression was positively correlated with the expressions of PD-L1, CTLA4, and PDCD1 in the TCGA cohort, a strong association between FGFBP1 and PD-L1 expression was only detected in BCG cohort (r=0.750). Furthermore, elevated FGFBP1 was observed in BCa cell lines and tissues in comparison to corresponding normal controls by RT-qPCR, western blotting, and immunohistochemical staining. Increased FGFBP1 was further detected in the failures than in the responders by immunohistochemical staining. Notably, FGFBP1 is positively associated with PD-L1 expression in BCa patients with BCG treatment. To sum up, FGFBP1 in BCa tissue could be identified as a promising biomarker for the accurate prediction of BCG response in BCa.